Mastering Windows 2000 registry - Hipson, Peter D. (Sybex, 2000)
Provides focused coverage of Windows most important, and challenging, element: the registry. Text will demystify the Windows Registry, optimize performance, avoid disasters, fix problems, and includes invaluable reference to registry keys, enteries, and data types. Softcover.